Evaluation of microalgae and cyanobacteria as potential sources of antimicrobial compounds - Faisal Alsenani; Karnaker R. Tupally; Elvis T. Chua; Eladl Eltanahy; Hamed Alsufyani; Harendra S. Parekh; Peer M. Schenk (Elsevier, 2020)
In recent decades, marine microorganisms have become known for their ability to produce a wide variety of secondary bioactive metabolites. Several compounds have been isolated from marine microorganisms for the development of novel bioactives for the food and pharmaceutical industries. In this study, a number of microalgae were evaluated for their antimicrobial activity against gram-positive and gram-negative bacteria, including food and plant pathogens, using various extraction techniques and antimicrobial assays. Disc diffusion and spot-on-lawn assays were conducted to confirm the antimicrobial activity. To measure the potency of the extracts, minimum inhibition concentrations (MIultCs) were measured. Three microalgae, namely Isochrysis galbana, Scenedesmus sp. NT8c, and Chlorella sp. FN1, showed strong inhibitory activity preferentially against gram-positive bacteria. These microalgal species were then selected for further purification and analysis, leading to compound identification. By using a mixture of different chromatography techniques gas chromatography-mass spectrometry (GC-MS) and high-performance liquid chromatography (HPLC) and ultra-high performance liquid chromatography-quadrupole time-of-flight mass spectrometry (UHPLC-Q-TOF-MS), we were able to separate and identify the dominant compounds that are responsible for the inhibitory activity. Additionally, nuclear magnetic resonance (NMR) was used to confirm the presence of these compounds. The dominant compounds that were identified and purified in the extracts are linoleic acid, oleic acid, docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA). These compounds are the potential candidates that inhibit the growth of gram-positive bacteria. This indicates the potential use of microalgae and their antimicrobial compounds as biocontrol agents against food and plant pathogens.